ANALISIS TINGKAT KERAWANAN BENCANA BANJIR DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Widya Septianingsih; Paus Iskarni (JURNAL GEOGRAFI, 2021)
This research aims to 1) know the distribution of floods in Rambah Subdistrict. 2) know the Level of Flood Insecurity 3) know the linkage of existing landuse to flood-prone areas. The data analysis techniques used are score and weighting with the paimin method using ArcGIS 10.4 software. Research Results 1) Flood distribution in Rambah District has 3 classes prone to flooding, low class 73.78% moderate class 19.15% high prone class 7.06% 2) Flood Insecurity Level based on Rainfall, Slope, Height, Soil Texture, Soil Drainage Permeability, Land Use, River is obtained the results of classification of 3 classes, not prone 15123.36 Ha, vulnerable class 12585.39 Ha and very vulnerable class 6749.59 Ha. 3) The linkage of land use with non-vulnerable flood insecurity is forest 5720.67Ha and the lowest settlement is 0.55Ha. shrub for vulnerable class 1974.8 Ha class is very prone plantation 2913.19 Ha, flood settlements are very prone 939.48 Ha.